1999
DOI: 10.1021/bi9827767
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Inhibition of the Nicotinic Acetylcholine Receptor by the Anticonvulsant MK-801 Investigated by Laser-Pulse Photolysis in the Microsecond-to-Millisecond Time Region

Abstract: The mechanism of inhibition of the muscle nicotinic acetylcholine receptor is of interest because of the many drugs which are known to modify its function. The laser-pulse photolysis technique, using a photolabile, biologically inert ligand (caged carbamoylcholine) for the nicotinic acetylcholine receptor, and BC3H1 cells have been used to investigate the mechanism of inhibition of the receptor by MK-801 [(+)-dizocilpine] in the microsecond-to-millisecond time region. MK-801 is an anticonvulsant and a known in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 35 publications
5
59
0
Order By: Relevance
“…These results can be understood in the light of transient kinetic results obtained previously (6). The earlier results indicated that the muscle-type AChR in BC 3 H1 cells has two inhibitory sites for MK-801; one site equilibrates with MK-801 within 50 ms and the second site within 4 s (6) Fig. 1) to a receptor form that does not conduct ions was observed (6,9,29,30).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…These results can be understood in the light of transient kinetic results obtained previously (6). The earlier results indicated that the muscle-type AChR in BC 3 H1 cells has two inhibitory sites for MK-801; one site equilibrates with MK-801 within 50 ms and the second site within 4 s (6) Fig. 1) to a receptor form that does not conduct ions was observed (6,9,29,30).…”
Section: Resultssupporting
confidence: 57%
“…3 A and B), all of the inhibition by MK-801 was relieved in the presence of 2 M aptamer II-3. These results can be understood in the light of transient kinetic results obtained previously (6). The earlier results indicated that the muscle-type AChR in BC 3 H1 cells has two inhibitory sites for MK-801; one site equilibrates with MK-801 within 50 ms and the second site within 4 s (6) Fig.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations